Asian Economic Integration: ASEAN+3+1 or ASEAN+1s? - Amita Batra (Indian Council for Research on International Economic Relations (ICRIER), 2006)
In this paper an attempt is made to evaluate the most efficient approach to regional economic integration in Asia. For the purpose, Asia is defined as inclusive of ASEAN, the plus three economies of China, Japan, Korea and India that is the ASEAN plus four. Given that ASEAN is an existing regional bloc in Asia, alternative approaches to the alignment of the plus four economies with ASEAN for the formation of the ASEAN+4 trade bloc have been evaluated to determine if there are efficiency costs by way of distortion in the patterns of trade away from those expected on the basis of comparative advantage. The findings of our analysis underscore the efficiency of a prior alignment with ASEAN for all the plus four economies.
Keywords: F13; F14; F15; 330; regional economic integration; Asia; efficiency cost; comparative advantage; first mover advantage; trade diversion.